Overview on natural dyes and their IR-spectra – Part I: Plant based dyes with naphthoquinone and anthraquinone structure - Boris Mahltig (Communications in Development and Assembling of Textile Products)
This is the first paper of a series of review articles reporting on natural dyes, their origin and infrared spectra (IR spectra). One aim of this review series is to compare IR spectra of natural dyes from different origin and discuss if this spectroscopic method can be used as versatile tool for the identification of natural dyes and their origin. This part I of the review series is related to four natural dyes based on the chemical structures of naphthoquinone and anthraquinone. Especially discussed are Lawson, juglone and alizarin, which are related to the natural products henna, walnut hull and madder root. Also, the natural dye based on alkanna root is investigated. Compared are the IR spectra of these natural dyes gained from different suppliers with the IR spectra of the pure chemical substances related to the natural dyes. A discussion with spectra from literature is supported. The aim of this review paper is to support infrared spectroscopic data of natural materials (natural dyes) to enable further material identification and also quality control supporting people working in the fields of fiber analytics or with production processes using natural dyes